Application of tobacco stems briquetting in tobacco flue-curing in rural area of China - Xinfeng, Wang; Guizhuan, Xu; Bailiang, Zhang; Youzhou, Jiao; Haifeng, Lu; Baoming, Li (International Journal of Agricultural and Biological Engineering, 2015)
To reduce the conventional energy consumption in rural area of China, tobacco stems briquetting (TSB) was used as fuel during the process of tobacco flue-curing, compared with honeycomb briquette (HB). Three fire furnaces with different heat exchangers using TSB were compared using the tobacco flue-curing. The results showed that the smog temperature of TSB was higher than that of HB, the efficiency of bio-fuel system with TSB was from 43.5% to 54%, while the efficiency of traditional fuel system was 51.5%. And the cost of tobacco flue-curing per hectare with TSB and HB was $750.0 and $1282.5, respectively. It is proved that TSB is an alternative choice using for the industry of tobacco flue-curing, and the improvement in the structure of fire furnace could optimize the process of tobacco flue-curing.Keywords: biomass, briquetting, tobacco flue-curing, bio-fuel, fire furnaceDOI: 10.3965/j.ijabe.20150806.1842Citation: Wang X F, Xu G Z, Zhang B L, Jiao Y Z, Lu H F, Li B M. Application of tobacco stems briquetting in tobacco flue-curing in rural area of China. Int J Agric & Biol Eng, 2015; 8(6): 84－88.